2005
DOI: 10.1007/s00497-005-0005-1
|View full text |Cite
|
Sign up to set email alerts
|

Microgametogenesis in Plumbago zeylanica (Plumbaginaceae). 2. Quantitative cell and organelle dynamics of the male reproductive cell lineage

Abstract: Quantitative cell and organelle dynamics of the male gamete-producing lineage of Plumbago zeylanica were examined using serial transmission electron microscopic reconstruction at five stages of development from generative cell inception to sperm cell maturity. The founder population of generative cell organelles includes an average of 3.88 plastids, 54.9 mitochondria, and 3.7 vacuoles. During development the volume of the pollen grain increases from 6,200 lm 3 in early microspores to 115,000 lm 3 at anthesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…Pollen proteins identified in this study are likely to be predominent in the vegetative cell, since sperm cells contain few organelles and a small cellular volume, e.g., less than 0.05% of the pollen volume in Plumbago (Russell and Strout 2005), and proportionately fewer transcript copies (Xu et al 1999;Engel et al 2003). Using the Gene Ontology annotation for Arabidopsis (Berardini et al 2004), the relative distribution of identified proteins (Table 1) associated with various cell components is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Pollen proteins identified in this study are likely to be predominent in the vegetative cell, since sperm cells contain few organelles and a small cellular volume, e.g., less than 0.05% of the pollen volume in Plumbago (Russell and Strout 2005), and proportionately fewer transcript copies (Xu et al 1999;Engel et al 2003). Using the Gene Ontology annotation for Arabidopsis (Berardini et al 2004), the relative distribution of identified proteins (Table 1) associated with various cell components is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, little is known about the morphology and role of vacuoles in sperm cells. Their existence has been documented using electron microscopy in a few plant species (Weber, 1988;Yu et al, 1992;Russell and Strout, 2005), and expression of two soluble E subunits of vacuolar H + -ATPase has been reported in the tonoplast of Arabidopsis (Arabidopsis thaliana) sperm cells (Strompen et al, 2005).…”
mentioning
confidence: 99%
“…Pollen grains of angiosperms contain a large vegetative cell and one generative cell giving rise to one or two sperm cells (Brewbaker, 1967). Although the sperm shows an occasional absence of plastids, pollen grains harbor most of the typical organelles of plant cells (Van Aelst et al, 1993;Yamamoto et al, 2003;Russell and Strout, 2005;Matsushima et al, 2008;Tang et al, 2009). The maturation process of pollen grains associates multiple steps in the formation and differentiation of vacuoles (vacuolation; for review, see Pacini et al, 2011).…”
mentioning
confidence: 99%
“…The difference in nuclear length between Svn and Sua increased with extended culture time from 12 to 24 h. The patterns of dimorphism in sperm cells in the MGUs, in terms of cell shape, have been reported to vary among species: the volume and surface area of Svn are greater than those of Sua in P. zeylanica (Russell 1984) and Torenia fournieri (Chen et al 2006), while the volume of the Sua is greater than that of Svn in N. tabacum (Tian et al 2001). Moreover, in the case of N. tabacum, dimorphism arises late during sperm development (Tian et al 2001), whereas in Plumbago zeylanica, it progressively advanced during development (Russell and Strout 2005). We propose that sperm dimorphism in C. mackenii follows the pattern of Nicotiana, as changes occur in Sua characteristics during sperm maturation.…”
Section: Discussionmentioning
confidence: 70%
“…4 Generative cells and sperm cells have many structural features that are distinct from somatic cells (Southworth and Cresti 1997). From an early stage, generative cells become spindle shaped and shed cytoplasm (Russell and Strout 2005). The microtubular cytoskeleton of generative cells and sperm cells differs from that of somatic cells: in maturing male germ cells, microtubules are typically arranged in prominent bundles that are aligned helically or longitudinally relative to the long axis of the cell (Palevitz and Tiezzi 1992;Southworth and Cresti 1997).…”
Section: Introductionmentioning
confidence: 99%